The potential of local cassava yields as a food source in West Papua - Sinaga Apresus; Purnomo Joko; Nambela Junita Br; Hendri Jon (BIO Web of Conferences)
Cassava is one of the staple foods and a source of food for the community. This study investigates the impact of various local cassava varieties on their growth and production. The parameters observed in this study include growth and yield indicators, stem diameter, plant height, total biomass weight in the ground, and fresh tube weight per plant. The study was designed using three treatments and three replications Randomized Block Design (RBD). Treatment consisted of varieties A, B, and C. The study results show that the total weight of biomass above ground was significant, with the highest weight of variety C at 4.15 kg, followed by B at 2.45 kg, and A at 1.78 kg. The fresh weight per plant has no significant differences, and the highest values were found in C (3.81 kg), followed by A (2.91 kg) and B (2.38kg). The local cassava varieties A, B, and C produced tuber quantities of 58.20 tonnes per hectare, 47.67 tonnes per hectare, and 76.16 tonnes per hectare respectively. Cassava production from these three local varieties has great potential to be developed as a food source for the community.